1975
DOI: 10.1007/bf00388064
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in pollen and its incorporation into seeds

Abstract: A study on the distribution of radioactive zinc ((65)Zn) in flowers of Vicia faba L. and Nicotiana tabacum L. showed the highest activity, expressed as cpm/mg dry weight, in pollen Also, using a histochemical method, it was observed that a portion of the naturally occurring zinc present in pollen grains was transferred into their growing tubes during germination. Calculations in based on the specific activity in (65)Zn-labelled pollen grains and in seeds from flowers pollinated with this pollen showed that abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…When Zn is no longer applied to fully fertile plants rescued by Zn supplementation, infertility is the first visible effect (data not shown). This is consistent with the measurement of high Zn concentrations in pollen of bean (Phaseolus vulgaris) and tobacco (Nicotiana tabacum), much of which was incorporated into embryos at fertilization (Polar, 1975). The HMA2p-GUS and HMA4p-GUS constructs are both expressed in developing anthers, particularly the tapetum, and RT-PCR experiments have confirmed expression of both HMA2 and HMA4 mRNA in this tissue.…”
Section: Discussionsupporting
confidence: 87%
“…When Zn is no longer applied to fully fertile plants rescued by Zn supplementation, infertility is the first visible effect (data not shown). This is consistent with the measurement of high Zn concentrations in pollen of bean (Phaseolus vulgaris) and tobacco (Nicotiana tabacum), much of which was incorporated into embryos at fertilization (Polar, 1975). The HMA2p-GUS and HMA4p-GUS constructs are both expressed in developing anthers, particularly the tapetum, and RT-PCR experiments have confirmed expression of both HMA2 and HMA4 mRNA in this tissue.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, Zn is present in pollen grains. [56] Furthermore, we found that Cu and Zn, which are considered to be emitted from metallurgical industrial activity, [52] are associated with different factors obtained from Varimax rotated factor analysis of trace metals (see Table 3).…”
Section: Nh 4 + and K + : Biomass Burning Emissionsmentioning
confidence: 92%